Reaksi Pasar terhadap Penerapan Pembatasan Sosial Berskala Besar pada Masa Pandemi Covid-19 - Purnayasa, I Wayan Agus; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 31 No 12 (2021), 2021)
On April 6, 2020, the government approved the implementation of the first Large-Scale Social Restrictions (PSBB) in Indonesia in the context of accelerating the handling of the Covid-19 pandemic. This study uses this event as an event under study to observe the market reaction before and after it, with a window period of 11 days. The average abnormal return and the average trading volume activity of stocks are used as indicators of market reaction. The study was conducted on 152 trading, service and investment sector companies listed on the Indonesia Stock Exchange (IDX), which were determined using a non-probability sampling method with a purposive sampling technique. Data were analyzed by using paired sample t-test and Wilcoxon signed rank test. The results showed that there was no difference between the average abnormal return and the average trading volume activity before and after the first PSBB was approved in Indonesia. The absence of market reaction is assumed because the level of market efficiency in Indonesia is still weak. Keywords : Covid-19 ; Social Distancing Policy; Market Reaction; Abnormal Return; Trading Volume Activity.